2011
DOI: 10.1016/j.pcl.2011.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Sweetener Use Among Children: Epidemiology, Recommendations, Metabolic Outcomes, and Future Directions

Abstract: Synopsis This review summarizes the existing literature pertaining to the epidemiology and current recommendations for pediatric artificial sweetener use and presents the results of studies investigating metabolic responses to artificial sweeteners among children. Observational and interventional studies testing the effects of artificial sweeteners on body weight, short-term satiety, glycemia, and glucoregulatory hormones are described. In addition, this review touches on the growing body of literature about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 68 publications
1
51
0
5
Order By: Relevance
“…Based on these data, it was concluded that the sweetener was responsible for this increase in weight gain and food intake did not. These data corroborate the studies by Sylvetsky et al (2011), who demonstrated a positive association between the consumption of artificial sweeteners and weight gain in children.…”
Section: Discussionsupporting
confidence: 92%
“…Based on these data, it was concluded that the sweetener was responsible for this increase in weight gain and food intake did not. These data corroborate the studies by Sylvetsky et al (2011), who demonstrated a positive association between the consumption of artificial sweeteners and weight gain in children.…”
Section: Discussionsupporting
confidence: 92%
“…17 In adults, NNS intake has paradoxically been associated with weight gain, incident obesity, and increased fat mass. 11,18,19 However, long-term studies of prenatal or early-life NNS exposure are rare, 20,21 and a systematic review in 2010 22 was inconclusive regarding metabolic effects of NNSs in children. Moreover, that review 22 did not focus on long-term effects or assess study quality, and several studies have since been published.…”
mentioning
confidence: 99%
“…6,7 Hence estimates of artificial sweetener consumption in the study were quantified from items listing 'diet soft drinks (diet soda) and use of pellets in beverages (tea/coffee/milk). Other beverages were not included in the study because of their low frequency of consumption.…”
Section: Dietary Assessmentmentioning
confidence: 99%